Safety Issues Concerning the Medical Use of Cannabis and Cannabinoids - Mark A Ware; Vivianne L Tawfik (Pain Research and Management)
Safety issues are a major barrier to the use of cannabis and cannabinoid medications for clinical purposes. Information on the safety of herbal cannabis may be derived from studies of recreational cannabis use, but cannabis exposure and effects may differ widely between medical and recreational cannabis users. Standardized, quality-controlled cannabinoid products are available in Canada, and safety profiles of approved medications are available through the Canadian formulary. In the present article, the evidence behind major safety issues related to cannabis use is summarized, with the aim of promoting informed dialogue between physicians and patients in whom cannabinoid therapy is being considered. Caution is advised in interpreting these data, because clinical experience with cannabinoid use is in the early stages. There is a need for long-term safety monitoring of patients using cannabinoids for a wide variety of conditions, to further guide therapeutic decisions and public policy.